Boundary land: diversity as a defining feature of the Digital Humanities - del Rio, María Gimena (2016)
he theme of this session is the Digital Humanities as a ?Boundary Land? - i.e. a locus in which such objects are common. As O´Donnell argues in his paper, this aspect is one of the defining features of contemporary Digital Humanities and an important cause of its recent rapid growth. As the field grows, DH workshops, panels, and journals see increasing work by practitioners trained in more and more traditionally distinct disciplinary traditions: textual scholars, literary critics, historians, New Media specialists, as well as theologians, computer scientists, archaeologists, Cultural Heritage specialists... and geographers, physicists, biologists, and medical professionals.It is the contention of the speakers of this panel that interpersonal diversity (i.e. diversity along lines such as gender, ethnicity, sexual orientation, language, economic region, etc.) is as an important element of this aspect of DH. The Digital Humanities is not only a place where different disciplines work together (and at times at odds to each other): it is also a place where different people work together and at odds in developing our field. In other words, diversity initiatives in the Digital Humanities are important not only because they let more people into our field, they are important because they change the nature of our field as its practice widens.The papers in this session each approach the issue from a different perspective. In the first paper, O?Donnell looks at the theoretical background to this understanding of diversity as a component of DH as a boundary discipline, grounding his approach in early work on interdisciplinarity and boundary work. In the second paper, Murray Ray and Bordalejo discuss the ways in which efforts to promote diversity within DH can paradoxically undermine its theoretical importance to the field, before turning to different examples of diversity´s intellectual importance. In the third paper, del Rio and González-Blanco examine the institutional and social pressures that promote and hinder dialogue among researchers in developing and developed countries and across linguistic and other boundaries before proposing new approaches in Digital Humanities that go beyond lingüistic diversity focusing on theories such as Sociology of Culture and Education and other reformulations.